The Arab Spring and Democratization; Why is Syria Different? - Ahmad Sahide (Sospol : Jurnal Sosial Politik, 2017)
AbstractThe Arab Spring is the momentum of the rise of the political power in the Middle East. It brought hope to have political power, namely democracy. So the people power demanded democracy for their life. Syria is one of the states impacted by the Arab Spring where the regime is shaken by this political turbulence.In this paper, it’s said that the democratization in Syria failed before the successfulness of the people in overthrowing Assad’s regime. Syria is different from Tunisia which succeeded in consolidating democracy. Syria is also different from Egypt which succeeded in consolidating democracy and passing background condition, even though failed in the prefatory fase (second step of the democratization). Here, it’s found that one of the factors why the democratization in Syria failed is the foreign intervention. Two biggest states are contesting in having influence and control in Syria, those are United States of America and Russia.Keywords: Arab Spring, Democracy, failure, foreign intervention, Syria, AbstrakArab Spring merupakan momentum kebangkitan kekuatan politik di Timur Tengah. Momentum tersebut membawa harapan berupa munculnya demokrasi. Dengan demikian, selama berlangsungnya Arab Spring, rakyat terus berupaya mendesak pemerintah agar demokrasi diterapkan. Suriah merupakan salah satu negara yang terkena  dampak  Arab Spring. Tulisan ini menyebutkan bahwa proses demokratisasi di Suriah telah gagal sebelum jatuhnya rezim Assad. Suriah berbeda dengan Tunisia yang berhasil dalam konsolidasi demokrasi. Suriah juga berbeda dengan Mesir yang berhasil dalam konsolidasi demokrasi dan melewati kondisi latar belakang, meskipun gagal dalam fase Pendahuluan (langkah kedua dari demokratisasi). Dari sini, telah ditemukan bahwa salah satu faktor kegagalan demokratisasi di Suriah ialah adanya intervensi asing. Terdapat dua terbesar negara besar yang bertarung dalam mendapatkan pengaruh dan kontrol di Suriah, yaitu Amerika Serikat dan Rusia.Kata Kunci:Arab Spring, Demokrasi, Intervensi Asing, Kegagalan, Suriah.